2018
DOI: 10.1001/jamapediatrics.2017.3884
|View full text |Cite
|
Sign up to set email alerts
|

Association of Salivary MicroRNA Changes With Prolonged Concussion Symptoms

Abstract: IMPORTANCE Approximately one-third of children who experience a concussion develop prolonged concussion symptoms. To our knowledge, there are currently no objective or easily administered tests for predicting prolonged concussion symptoms. Several studies have identified alterations in epigenetic molecules known as microRNAs (miRNAs) following traumatic brain injury. No studies have examined whether miRNA expression can detect prolonged concussion symptoms. OBJECTIVE To evaluate the efficacy of salivary miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 35 publications
1
86
0
Order By: Relevance
“…Moreover, the levels of miR-29a-3p were decreased in whole blood [ 76 ] and those of miR-141-3p in serum of Parkinson’s patients [ 77 ]. Levels of let-7b-5p were decreased in the saliva of children with mild traumatic brain injury [ 78 ]. Intriguingly, a downregulation of miR-451a and miR-16-5p was also identified in peripheral blood of ASD children [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the levels of miR-29a-3p were decreased in whole blood [ 76 ] and those of miR-141-3p in serum of Parkinson’s patients [ 77 ]. Levels of let-7b-5p were decreased in the saliva of children with mild traumatic brain injury [ 78 ]. Intriguingly, a downregulation of miR-451a and miR-16-5p was also identified in peripheral blood of ASD children [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that perturbation in miRNA signaling after traumatic brain injury results in overlapping miRNA profiles in cerebrospinal fluid and saliva [ 31 ]. Further, we demonstrated that disruptions in salivary miRNA levels can persist for weeks after initial injury [ 32 ], and predict the occurrence of persistent post-concussive symptoms [ 33 ]. The purpose of the current study was to determine whether non-invasive salivary measurement of miRNAs could provide insights into the pathobiology of repetitive concussions among professional football athletes.…”
Section: Introductionmentioning
confidence: 99%
“…We sorted out miR‐769‐5p from 10 miRNAs shared by SPAG5‐AS1 and YY1 because it was downregulated by HG in HPCs and interacted with SPAG5‐AS1. Former studies showed that miR‐769‐5p participated in prolonged concussion symptoms and acted a predictor of lung cancer patient survival . However, this was the first time for miR‐769‐5p to be related to HG‐induced podocyte injury.…”
Section: Discussionmentioning
confidence: 97%